Temporal trends and determinants of COVID-19 vaccine series initiation after recent pregnancy - Eszter Török; Tavleen Dhinsa; Sheryll Dimanlig-Cruz; Gillian D. Alton; Ann E. Sprague; Sandra I. Dunn; Prakesh S. Shah; Darine El-Chaâr; Annette K. Regan; Kumanan Wilson; Sarah A. Buchan; Jeffrey C. Kwong; et al. (Taylor & Francis Group, 2023)
During the rapid deployment of COVID-19 vaccines in 2021, safety concerns may have led some pregnant individuals to postpone vaccination until after giving birth. This study aimed to describe temporal patterns and factors associated with COVID-19 vaccine series initiation after recent pregnancy in Ontario, Canada. Using the provincial birth registry linked with the COVID-19 vaccine database, we identified all individuals who gave birth between January 1 and December 31, 2021, and had not yet been vaccinated by the end of pregnancy, and followed them to June 30, 2022 (follow-up ranged from 6 to 18 months). We used cumulative incidence curves to describe COVID-19 vaccine initiation after pregnancy and assessed associations with sociodemographic, pregnancy-related, and health behavioral factors using Cox proportional hazards regression to estimate adjusted hazard ratios (aHR) and 95% confidence intervals (CI). Among 137,198 individuals who gave birth in 2021, 87,376 (63.7%) remained unvaccinated at the end of pregnancy; of these, 65.0% initiated COVID-19 vaccination by June 30, 2022. Lower maternal age (<25 vs. 30-34 y aHR: 0.73, 95%CI: 0.70-0.77), smoking during pregnancy (vs. nonsmoking aHR: 0.68, 95%CI: 0.65-0.72), lower neighborhood income (lowest quintile vs. highest aHR: 0.79, 95%CI: 0.76-0.83), higher material deprivation (highest quintile vs. lowest aHR: 0.74, 95%CI: 0.70-0.79), and exclusive breastfeeding (vs. other feeding aHR: 0.81, 95%CI: 0.79-0.84) were associated with lower likelihood of vaccine initiation. Among unvaccinated individuals who gave birth in 2021, COVID-19 vaccine initiation after pregnancy reached 65% by June 30, 2022, suggesting persistent issues with vaccine hesitancy and/or access to vaccination in this population.